A // Wir gehören zusammen: Ja zum Partnerschaftsgesetz am 22. September
soziale Fragen;Familie (allgemein);Familienrecht;Ehe;Eherecht soziale Fragen;Familie (allgemein);Familienstand;gleichgeschlechtliches Paar politischer Rahmen;Wahlen und Abstimmungen;Volksabstimmung